Effects of (Pre-)analytical Variables on Activated Protein C Resistance Determined Via a Thrombin Generation-based Assay - Curvers, Joyce; Christella, M.; Thomassen, G. D. L.; de Ronde, Hans; Bertina, Rogier M.; Rosendaal, Frits R.; Tans, Guido; Rosing, Jan (Thrombosis and Haemostasis, 2002)
The normalized activated protein C sensitivity ratio (nAPC-sr) determined with an assay that quantifies the effect of APC on thrombin formation initiated via the extrinsic coagulation pathway identifies hereditary and acquired defects of the protein C system. We investigated the influence of assay conditions (analytical variables) and plasma handling (pre-analytical variables) on nAPC-sr obtained with this APC resistance test. The effect of the analytical variables (CaCl2, phospholipid and APC concentrations and the concentration and source of tissue factor) was determined in pooled normal plasma. Inhibition of thrombin formation by APC was dependent on the APC concentration and was also affected by the tissue factor, Ca2+ and phospholipid concentrations. Thus, strict standardization of reactant concentrations is required to obtain reproducible nAPC-sr. Three different tissue factor preparations were compared by determining nAPCsr in plasma samples obtained from 90 healthy individuals. nAPC-sr were similar for all three tissue factor preparations although, compared with the noncommercially available tissue factor used in earlier studies, values determined with commercial tissue factor preparations showed larger variation. Pre-analytical variables, investigated in plasma of nine volunteers (3 normal individuals and 6 individuals with an APCresistant phenotype) were: concentration of anticoagulant (3.2% vs. 3.8% trisodiumcitrate), time before processing of blood (0, 4 and 24 h), centrifugation speed, storage temperature of plasma (–20° C vs. –80° C) and sample thawing. Multiple linear regression analysis showed that only the citrate concentration affected the nAPC-sr, which was higher in samples collected in 3.2% trisodiumcitrate than in samples collected in 3.8% trisodiumcitrate.
Keywords: APC Resistance; Factor VLeiden